The Effect of Air Injection for Formation of Radicals in Liquid Glow Discharge Plasma Electrolysis with K2SO4 Solution - Harianingsih, Harianingsih; Rengga, Woro Dyah Pita; Kusumaningrum, Maharani; Imani, Nadya Alfa Cahaya; Saksono, Nelson; Zakaria, Zainal (Reaktor, 2023)
Glow discharge is part of the phenomenon of plasma formation on the electrode side in contact with the electrolyte solution and begins with an electrolysis reaction with direct electric current. In this research, 0.02 M K2SO4 electrolyte was used, the anode in the form of tungsten and stainless steel for the cathode in a direct current plasma electrolysis reactor. The phenomenon of plasma formation is explained using a strong current and voltage characteristic curve. There are three plasma formation zones: the ohmic zone, the transition zone and the glow discharge plasma zone. Air injection affects the formation of glow discharge plasma and radicals. Without the injection of air, radicals formed only •OH, •H and •O with emission intensities of 20012 a.u, 10121 a.u and 10245 a.u. Air injection 0.8 L men-1 produced radicals •OH, •N, •N2*, •N2+, •H and •O with emission intensities of 30863a.u, 20139 a.u, 28540 a.u, 18023 a.u, 12547 a.u and 49800 a.u. Many radicals are generated when the plasma reaches stability. The plasma is dominated by H2O ionization, and the plasma is more stable if formed in the gas phase. Other results from this research at 0 L men-1, 0.2 L men-1, 0.4 L men-1 and 0.8 L men-1 stable plasma were formed at 675 V, 660 V, 650 V and 650 V. The plasma that can be seen from the bright light, the injection of air accelerates the formation of a gas envelope to reduce energy.